A triple‐layer dual‐bandpass frequency selective surface of third order response with equivalent circuit analysis. Issue 2 (15th November 2019) - Chatterjee, Ayan; Parui, Susanta K.
Abstract: A multilayered cascaded and polarization‐dependent frequency selective surface (FSS) exhibiting dual bandpass frequency response is proposed in this article. The FSS is composed of two metal‐based square patch layers in the two ends and one aperture type layer in the middle, separated by two dielectric substrates. The FSS exhibits bandpass response of third order with two transmission poles in the 5‐6 GHz band and one pole at 2.5 GHz. The passbands are separated well enough with a transmission zero at 3.5 GHz leading to significant out‐of‐band rejection. The structure is ultrathin with the thickness on the order of 0.01λ0 with respect to the lowest resonating frequency. It is shown with parametric studies how the poles can be tuned individually. Principle of operation of the FSS is explained with its equivalent circuit model. Transmission phase of the FSS varies linearly with frequency in the upper band. Simulation result is verified experimentally for the fabricated prototype.